A Parallel Algorithm of Non-Linear Fluid-Solid Coupling Problem for Hydrofoil. Issue 3 (September 2014) - Chen, Xin; Sun, Zhenli; Zhang, Shesheng
A parallel algorithm of the non-linear hydrofoil fluid-solid coupling problem is discussed. Based on hydrodynamics and solid mechanics, a variational formula is derived on the mapping plane with a fixed boundary between solid and fluid, and calculated using both parallel finite element method and the finite difference method. The calculation steps of an example are given, and the numerical results of flat hydrofoil are presented.